2018
DOI: 10.1007/s10495-018-1446-y
|View full text |Cite
|
Sign up to set email alerts
|

Hypertonicity primes malignant melanoma cells for apoptosis

Abstract: The tumor environment critically influences responsiveness of cancer cells to chemotherapies, most of which activate the mitochondria-regulated (intrinsic) apoptotic cascade to kill malignant cells. Especially skin tumors encounter an environment with remarkable biophysical properties. Cutaneous accumulation of Na locally establishes osmotic pressure gradients in vivo (hypertonicity or hyperosmotic stress), but whether cutaneous hypertonicity is a factor that modulates the responsiveness of skin cancers to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 26 publications
0
6
0
1
Order By: Relevance
“…Moreover, there is evidence that increased extracellular Na + helps in antigen degradation [15] and fighting viral infections [16,17]. In addition, elevated Na + levels prime malignant cells for apoptosis [18,19] and augment the cytotoxic potential of death receptors in cancer cells [20]. However, the mechanism underlying enhanced antibacterial activity in MΦ is unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, there is evidence that increased extracellular Na + helps in antigen degradation [15] and fighting viral infections [16,17]. In addition, elevated Na + levels prime malignant cells for apoptosis [18,19] and augment the cytotoxic potential of death receptors in cancer cells [20]. However, the mechanism underlying enhanced antibacterial activity in MΦ is unclear.…”
Section: Introductionmentioning
confidence: 99%
“…This BH3-only protein determines sensitivity to BCL-XL targeting BH3 mimetics in various cancer entities 32,[38][39][40][41] . In previous work, we showed that hyperosmotic stress is capable to facilitate activation of the intrinsic apoptosis pathway [8][9][10]42 . However, in these studies we repeatedly failed to detect hypertonicity-induced disturbances in the BCL-2 protein family network.…”
Section: Discussionmentioning
confidence: 99%
“…In previous work, we showed that hyperosmotic stress facilitates MOMP induction [8][9][10] . Hyperosmotic stress (or hypertonicity) occurs when osmotically active solutes (such as NaCl) cannot passively diffuse across the plasma membrane and thus establish an osmotic pressure gradient between the extra-and intracellular space.…”
Section: Hyperosmotic Stress Renders Selective Bcl-xl Inhibition Suffmentioning
confidence: 93%
See 1 more Smart Citation
“…Other signaling pathways [25], melanoma-specific transcriptional regulators [26] and post-transcriptional control [27] also extensively contribute to the capability of melanoma cells to counteract unfavorable conditions, including exposition to anti-cancer therapies. In addition, microenvironment-mediated regulation of expression of pro-survival molecules, including MCL-1, BCL-X L , and BFL-1 [28][29][30], supports a remarkable adaptive capabilities of melanoma cells. Despite a tremendous advances in the therapeutic options for melanoma patients (Figure 1), inability or limited vulnerability of melanoma cells to induction of apoptosis in response to inhibitors of BRAF mut (BRAFi) and MEK (MEKi) [31][32][33][34][35][36][37][38], and escape from immunotherapy [39][40][41] are the reasons for re-growth of drug-resistant disease.…”
Section: Introductionmentioning
confidence: 97%